2014
DOI: 10.12659/aot.892095
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Treated Bacterial Infections within One Month before Living Donor Liver Transplantation in Adults

Abstract: Background:The impact of treated preoperative bacterial infections on the outcome of living-donor liver transplantation (LDLT) is not well defined. The aim of this study was to determine the frequency of pre-transplant bacterial infections within one month before LDLT and their impact on the post-transplant morbidity and mortality. Material/Methods:We retrospectively reviewed the records of 50 adult LDLT recipients between January 2009 and October 2011. Patients were divided into two groups based on whether th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 14 publications
0
4
0
1
Order By: Relevance
“…IgG had mild positive correlations with CD19, CD20, and CD22 at 4 weeks after LDLT (r=0.34, p=0.043; r=0.36, p=0.032; r=0.37, p=0.026, respectively). [8][9][10][11][12][13][14][15][16][17][18][19] mg/dL vs. 23 [18][19][20][21][22][23][24][25][26][27] mg/dL, p=0.0377). Although fresh frozen plasma contains complement components, including C3 and C4 (29), survivors had used both plasmapheresis and fresh frozen plasma with comparable frequency to non-survivors.…”
Section: Correlations Between Clinical Parameters and Laboratory Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…IgG had mild positive correlations with CD19, CD20, and CD22 at 4 weeks after LDLT (r=0.34, p=0.043; r=0.36, p=0.032; r=0.37, p=0.026, respectively). [8][9][10][11][12][13][14][15][16][17][18][19] mg/dL vs. 23 [18][19][20][21][22][23][24][25][26][27] mg/dL, p=0.0377). Although fresh frozen plasma contains complement components, including C3 and C4 (29), survivors had used both plasmapheresis and fresh frozen plasma with comparable frequency to non-survivors.…”
Section: Correlations Between Clinical Parameters and Laboratory Resultsmentioning
confidence: 99%
“…In ABO-incompatible LDLT cases, we used rituximab (375 mg/m 2 ) as an induction 10-14 days before LDLT and added mycophenolate mofetil (MMF) after LDLT. For patients who have renal dysfunction, trough levels of tacrolimus were intentionally kept lower by the administration of other immunosuppressants, including MMF and/or basiliximab (11).…”
Section: Immunosuppression Therapymentioning
confidence: 99%
“…Earlier studies found that patients with preoperative infection had higher rates of postoperative infection [5,6], and patients with preoperative bacterial infection often had higher baseline CRP levels, which is in agreement with our findings. However, the risk of infection in patients with previous infection was less than twofold that in patients without infection before LT (48% vs. 25% [6], 48% vs. 30.6% [5], and 85% vs. 63% [19]). In our study, the incidence of 30-day CSI in patients with a CRP level ≥ 9.48 mg/L was 36.1%, compared to 11.5% for those with a CRP level < 9.48 mg/L, the adjusted HR of CRP level ≥ 9.48 mg/L compared to a CRP level < 9.48 mg/L was 3.16 (95% CI 2.32-4.29, p < 0.001).…”
Section: Discussionmentioning
confidence: 87%
“…Bertuzzo et al20 reported that bacterial infection 1 month before LT was related to a higher rate of infection after transplantation, but did not lead to a worse outcome. Also, Hara et al21 reported that 20 patients who underwent LDLT with an infection 1 month before transplant had a lower 1-year post-transplant survival rate than patients without infection (65% versus 86%, respectively).…”
Section: Discussionmentioning
confidence: 99%